CFD-BASED DYNAMIC STABILITY DERIVATIVE PREDICTION OF BIPLANE TAILSITTER UAV WITH LINEAR AND HARMONIC MOTION MODELS - Diqnada, Dzikrian
This undergraduate thesis implements the application of a computational fluid dynamics (CFD) approach to predict the static and dynamic stability derivatives at the lateral-directional direction of the Fast and Efficient Autonomous Delivery (FEAD) UAV, a Quadrotor Biplane Tailsitter UAV. This novel airframe configuration is a suitable alternative for last-mile delivery missions in urban areas. The complex geometry design of the FEAD UAV has prompted further study of the stability derivative analysis. The versatility of the landing gear system as vertical tailplane at fixed-wing mode and landing gear at rotary wing mode must satisfy the aerodynamic and structural requirements at once. Aiming to obtain the stability derivatives, the unsteady aerodynamic simulation by applying reduced frequency is introduced in linear and harmonic forced motion models that give harmonic historical data of force and moment over time. For the two motion models, this study utilizes the triangle wave function and sinusoidal wave harmonic motion models. Then, the stability derivatives are obtained through the historical data process of the force and moments, utilizing the Fourier analysis. This study also investigates the comparison of stability derivatives between the triangle wave and the sinusoidal wave function motion models. This study also conducts parametric study of the stability derivative of the FEAD UAV are conducted by altering the reduced frequency.